The impact of foliage coverage on green facade towards urban heat island in Klang Valley - Kamaruzaman, Khairunnisa; Alias, Nur Ulfah Awatif Umairah; Ismail, Mohd Noorizhar; Sanusi, Aliyah Nur Zafirah; Yusof, Zeenat Begam (IFERP Explore, 2023)
The occurrence of urban heat islands has become a rising concern in densely populated places, particularly in Klang Valley. Strategies for mitigation are thus needed to reduce urban heat, particularly considering the rising of urbanization, global warming, and the frequency and intensity of heatwaves. The potential of green infrastructure is being evaluated on its effectiveness in mitigating urban heat island. Throughout this paper, the study investigates the influence of foliage coverage on green facades and its efficiency in mitigating urban heat islands in the Klang Valley. To do this, a thorough assessment of relevant literature is conducted, including a case study visit to a few buildings to study the relationship between green facades, foliage covering, and urban heat islands. According to the findings, green façade with more plant coverage provides significant benefits in terms of minimizing urban heat island impacts. Vegetation functions as a natural insulator, cooling ambient temperatures through reducing solar radiation absorption. Increased foliage coverage improves shading, evapotranspiration, and natural cooling, leading to lower energy use and better air quality.